Land law and the extractive industries : challenges and opportunities in africa - Nalule, victoria r (London [England] : HART PUBLISHING, 2021)
"This book analyses the nexus between land access and the extractive industries in Africa, specifically highlighting the gaps in energy, land and mining laws and the practical solutions needed to settle the increasing number of land disputes in resource-rich areas. Access to land is essential for the successful operation of energy and mining projects. However, there are often social, environmental and economic issues associated with acquiring land for these projects. Socially, many people are relocated; economically, local communities are not given adequate compensation; environmentally, pollution negatively impacts on the agricultural and fishing industries relied on by over 80% of the local communities. Against this stark background, and drawing from the author's fieldwork research, this book addresses the important question of whether the different land tenure systems, coupled with administration and registration procedures, are adequate to address the increasing land disputes in oil and mineral-rich African countries."--
Preface -- 1. Introduction to Land and Extractives in Africa -- 1.1. -- Introduction -- 1.2. Ownership and Control of Extractive Resources -- 1.3. Legal and regulatory frameworks governing the African Extractive Industries -- 1.4. Nexus between Land Access and Extractives -- 1.5. Structure of the Book -- 1.6. -- Conclusion -- 2. Land Law Reforms in Africa and Their Impact on the Extractive Industries -- 2.1. Introduction to Land Law in Africa -- 2.2. Land Law Reforms and Their Impact on the Extractive Industries: Case Studies -- 2.3. Environmental Impacts Associated with Extractives and Land Access -- 2.4. Conclusion -- 3. Land Access in the Perspective of the African Mining Sector -- 3.1. Introduction to Mining in Africa -- 3.2. Land Access in the Perspective of Large-Scale Mining -- 3.3. Land Access in the Perspective of Artisanal and Small-Scale Mining -- 3.4. Gender Justice and Mining: Impact of Land Tenure Systems -- 3.5. Mining Disputes and Land Access -- 3.6. Conclusion -- 4. Land Access in the Perspective of the African Energy Sector -- 4.1. Introduction to the African Energy Sector -- 4.2. Land Access in the Perspective of Petroleum Projects -- 4.3. Land Access in the Perspective of Renewable Energy Projects -- 4.4. Energy Disputes Related to Land -- 4.5. International Instruments and Good Governance -- 4.6. -- Conclusion -- 5. Other Pertinent Issues in the African Extractive Industry and Land Rights -- 5.1. Social Licence to Operate (SLO), Extractives and Land Access -- 5.2. Local Content, Extractives and Land Access -- 5.3. Regionalism, Extractives and Land Access -- 5.4. Concluding Remarks and Recommendations -- Bibliography -- Index.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Energy & natural resources law; Electronic books